2016
DOI: 10.1145/2948065
|View full text |Cite
|
Sign up to set email alerts
|

Trip Recommendation Meets Real-World Constraints

Abstract: As location-based social network (LBSN) services become increasingly popular, trip recommendation that recommends a sequence of points of interest (POIs) to visit for a user emerges as one of many important applications of LBSNs. Personalized trip recommendation tailors to users' specific tastes by learning from past check-in behaviors of users and their peers. Finding the optimal trip that maximizes user's experiences for a given time budget constraint is an NP-hard problem and previous solutions do not consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Yuan et al [10] found out that most users tend to visit different POIs at a different time in a day, and the check-in behaviors between neighbor time slots are similar. In addition to that, Zhang et al [27] pointed out that POI may be not available in all time, for example, POIs are only accessible during their opening hours. He et al [28] investigated the temporal popularity of a POI and the temporal check-in trends to provide personalized POI recommendation.…”
Section: Related Workmentioning
confidence: 99%
“…Yuan et al [10] found out that most users tend to visit different POIs at a different time in a day, and the check-in behaviors between neighbor time slots are similar. In addition to that, Zhang et al [27] pointed out that POI may be not available in all time, for example, POIs are only accessible during their opening hours. He et al [28] investigated the temporal popularity of a POI and the temporal check-in trends to provide personalized POI recommendation.…”
Section: Related Workmentioning
confidence: 99%
“…As mentioned in [9], it presents effective solutions to the constraints. Besides users can comment after visiting and from these comments other users may get help.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, trip planning should prepare an itinerary considering worst-case scenarios to satisfy constraints. In [26], Zhang et al studied tour recommendation considering POI availability and uncertain traveling times represented as random variables following some probability distributions. This approach is similar to our proposed model, but our probabilistic itinerary evaluation model expands modeling capabilities by including various uncertain factors, such as weather conditions, visit duration, and costs.…”
Section: Copyright Cmentioning
confidence: 99%